O estágio curricular no contexto da EaD : a relação entre teoria e prática na formação do pedagogo - Kuhn, Ana Paula (2019)
The relation theory and practice has been widely discussed in the Pedagogy Courses, with the Supervised Curricular Internship being an important element in the Teacher Training process. The Internship is understood as one of the spaces that allows the effective knowledge and knowledge required for teaching practice. Based on this understanding, this study sought to analyze how the relationship between theory and practice in the development process in the three Curricular Stages (Early Childhood Education, Elementary Education and Non-school Spaces) of the distance Pedagogy Course of the State University of Mato Grosso / DEAD / UNEMAT, offered by Universidade Aberta do Brasil / UAB at the Sapezal center. It was an exploratory qualitative approach. Throughout the research, the documentary analysis of the Pedagogical Political Project of the UNEMAT / UAB Pedagogy Course, of the regulation pertinent to the Curricular Internship, of the pedagogical practice carried out in the exercise of teaching and of the reflective reports constructed by the students in the process of initial formation was carried out. The research was carried out with a group of 15 students. The group was accompanied by a distance teacher and a faceto-face tutor. It has been the privilege to observe from the elaboration of the internship projects, the classroom interactions and the distance until the moment of the regency in the classroom in the three stages in the Course. With this research, we sought to contribute to the field of teacher education, specifically in relation to the Curricular Stages, to the extent that scenarios, knowledge, concepts and training methodologies are on the scene, considering the relevance of the university as a locus of articulated formation to the spaces of poles and schools. The results pointed out that the experience of the Curricular Internship needs to potentiate the exercise of critical reflection on the teaching practices and the teaching knowledge, which implies problematization and exchanges of experiences and knowledge for the collective work and for understanding the school as a singular context of teacher training. The analyzes were carried out considering the Project of the Pedagogy Course that corroborates with the thought of teacher as transforming intellectual, discussed by Giroux (1999). It is assumed that the supervised curricular stage has the fundamental function that is not only to take the theoretical knowledge to the field of practice, but to understand it, to elaborate it, thinking the reality lived by the future teacher.